P045 HIGH DIMENSIONAL IMMUNE PHENOTYPING AND TRANSCRIPTIONAL ANALYSES REVEAL ROBUST RECOVERY OF VIABLE HUMAN IMMUNE AND EPITHELIAL CELLS FROM CRYOPRESERVED INTESTINAL TISSUE. (18th January 2018) - Konnikova, Liza; Boschetti, Gilles; Rahman, Adeeb; Lord, James; Richmond, Camilla; Tomov, Vesselin; Gordon, Will; Jelinsky, Scott; Canavan, James; Wall, Sarah; Field, Michael; Zhou, Fanny; et al.
Abstract: Background: Simultaneous analyses of peripheral and mucosal immune compartments can yield insight into the pathogenesis of mucosal-associated diseases. Although methods to preserve peripheral immune cells are well established, studies involving mucosal immune cells have been hampered by lack of simple storage techniques. Methods: Here we provide a method to immediately cryopreserve intestinal tissue with retention of viability and functionality of both immune and epithelial cells allowing for subsequent transcriptional and cellular analysis. To test preservation of immune cells by this methodology, we employed mass cytometry to generate high-dementional maps of immune cells residing in the intestine. To test the ability of this methodology to preserve epithelial stem cells, we generated enteroids from cryopreserved tissue. Finally, to test the preservation of the transcriptome we employed RNAseq analysis. Results: We show that cryopreserved tissue can be used to (1) generate single cell suspensions of live immune cells with maintenance of immune make up and cytokine expression upon stimulation (Fig 1A-C) and (2) to generate enteroids (Fig 1 D-E). Furthermore, this methodology allows for preservation of the transcriptional profile of the tissue with retention of expression of differentially regulated genes (DEGs) between inflamed and uninflamed tissue (Fig 1 F-G). Finally, in a pilot cohort of IBD patients, we employ this protocol and mass cytometry for in depth immune analysis of cryopreserved GI tissue. This integrative approach not only allowed for validation of several hallmarks of Crohn's disease and ulcerative colitis but also the identification of novel mucosal cell populations distinguishing these two diseases (Fig 2). Conclusions: These methods will facilitate translational studies allowing for batch analysis of mucosal tissue to investigate diseases pathogenesis, biomarker discovery and treatment responsiveness.